The Art and Craft of Screenwriting: Practice and Prospects of Screenwriting in Pakistani Film - Ahmer Sohail (Journal of Peace, Development and Communication, 2021)
In filmmaking, screenplay plays the pivotal part, without which the idea of making film is absurd indeed. The academic learning of art and craft of screenwriting have actually been taken for granted in Pakistan. This overlooking serves one of the reasons owing to which Pakistani Cinema could not get along with its contemporaries. This qualitative study throws light on the significance of screenplay in the whole process of making a film and points out to the pedagogical needs of screenplay writing to be met in Pakistan through in-depth interviews of academician and practitioners of film and communication studies in Lahore. Keywords: Screenplay, Mise en scene, Storytelling, Pedagogy